Mediation as a law in force, not a dead letter. How to work out a common ground for theory and practice? - Knapczyk, Ewelina (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2018)
The subject of this paper is the institution of mediation, with a special emphasis on the formulation of postulates addressed to the Polish legislative, governmental institutions, local authorities, corporation of advocates, non-governmental organisations, and establishments of higher education. The Author outlines the general construction of mediation and the mechanisms of its functioning, the impact of the European Union on its Member States in the context of that institution, and touches upon the practical application of mediation in Poland, concluding that once the postulates enumerated in the paper have been addressed and realized, this will grossly reduce the piling number of unresolved disputes, and consequently will minimize the cost arising from the ever- -growing numbers of litigation and legal dispute.